Geotechnical investigation, landslide mechanism and countermeasure on the road above the soft-medium clay - Syah, Aminudin; Fikri Alami (Journal of Civil Engineering and Planning (JCEP), 2024)
A landslide event occurred in Sukarami, Lahat Regency, in early 2024. This study investigates the landslide mechanism, analyzes the influence of groundwater level rise and load on slope stability, and proposes a management concept. The methodology employed a landslide survey, soil investigation, and limit equilibrium-based stability analysis. Field investigations and surveys revealed that the landslide resulted from a decrease in the shear strength parameter of the surrounding soil layer triggered by rainfall and road drainage runoff. The slip plane, located within a soft to medium consistency clay layer, exhibits high susceptibility to water-induced instability. Numerical simulations demonstrated a negative correlation between groundwater level and slope safety factor, particularly when the water table reaches the critical slip plane. The implementation of a combined gabion, DPT, and minipile reinforcement system can enhance slope stability and elevate the safety factor to meet established standards. Notably, the addition of vehicle loads up to 30 kN/m2 exerted an insignificant influence on slope stability.